Agriculture urbaine : un outil multidimensionnel pour le développement des quartiers - Éric Duchemin; Fabien Wegmuller; Anne-Marie Legault (VertigO)
For over 30 years, different urban agriculture (UA) experiments have been undertaken in Montreal (Quebec, Canada). The Community Gardening Program, managed by the City, and 6 collective gardens, managed by community organizations, are discussed in this article. These experiments have different objectives, including food security, socialization and education. Although these have changed over time, they have also differed depending on geographic location (neighbourhood). The UA initiatives in Montreal have resulted in the development of a centre with a significant vegetable production and a socialization and education environment that fosters individual and collective social development in districts with a significant economically disadvantaged population. The various approaches attain the established objectives and these are multi-dimensional tools used for the social development of disadvantaged populations.